Genetic control of total phenolic content and some kernel compositional traits in purple maize (2022)
Purple maize kernels are rich in phytochemicals and nutrients which can be exploited to promote human health. A better understanding of the genetic mechanisms controlling these qualities, which could also be dependent on the choice of parents and their role in the cross, is important for their improvement. This study was conducted to: investigate the nature and relative importance of gene effects involved in the inheritance of total phenolic content (TPC) and proximate composition in reciprocal crosses between two maize lines (UIp01 and TZi3) with purple and white kernels, respectively using generation mean analysis. Kernels of F1, F2 and backcross generations derived from UIp01 × TZi3 and TZi3 × UIp01 and the parents were assessed for TPC and proximate composition following standard procedures. Analysis of variance revealed that the populations differed significantly for all traits, except moisture content. Reciprocal differences were observed only for TPC indicating the influence of maternal parent in its inheritance. Heritability estimates were moderate (0.4-0.5) to high (0.7-0.9) for most traits. Results showed the importance of non-additive effects over additive effects for starch and fat contents, and varying levels of additive and non-additive effects for TPC, moisture, protein, ash and fiber contents.